A conservation of resources view of the relationship between transformational leadership and emotional exhaustion: The role of extra effort and psychological detachment. Issue 3 (3rd July 2021) - Stein, Maie; Schümann, Marlies; Vincent-Höper, Sylvie
ABSTRACT: In this study, we draw on conservation of resources theory to suggest that transformational leaders' encouragement of extra effort in followers might reduce or increase followers' emotional exhaustion depending on their ability to replenish energy reserves. Specifically, we argue that the indirect relationship between transformational leadership (TFL) and followers' emotional exhaustion via extra effort varies depending on followers' levels of psychological detachment from work. We tested the hypothesised conditional indirect effect model using three-wave data from 214 employees working in various industries. Regression analyses showed that psychological detachment moderated the indirect relationship between TFL and emotional exhaustion through extra effort such that the indirect relationship was negative with high psychological detachment and positive with low psychological detachment. The findings of this study indicate the importance of recognising that the beneficial effects of TFL in reducing emotional exhaustion may not hold for all followers but are contingent on followers' levels of psychological detachment. Returning to one of the original premises of the TFL model, i.e. that transformational leaders bring about extra effort from followers, contributes to further understanding that TFL might have a dark side for employee well-being.